Automated disposable small scale reactor for high throughput bioprocess development: A proof of concept study. Issue 12 (1st July 2013) - Bareither, Rachel; Bargh, Neil; Oakeshott, Robert; Watts, Kathryn; Pollard, David
ABSTRACT The acceleration of bioprocess development for biologics and vaccines can be enabled by automated high throughput technologies. This will alleviate the significant resource burden from the multi‐factorial statistical experimentation required for controlling product quality attributes of complex biologics. Recent technology advances have improved clone evaluation and screening, but have struggled to combine the scale down criteria required for both high cell density cell culture and microbial processes, with sufficient automation and disposable technologies to accelerate process development. This article describes the proof of concept evaluations of an automated disposable small scale reactor for high throughput upstream process development. Characterization studies established the small scale stirred tank disposable 250 mL reactor as similar to those of lab and pilot scale. The reactor generated equivalent process performance for industrial biologics processes for therapeutic protein and monoclonal antibody production using CHO cell culture, Pichia pastoris and E. coli. This included similar growth, cell viability, product titer, and product quality. The technology was shown to be robust across multiple runs and met the requirements for the ability to run high cell density processes (>400 g/L wet cell weight) with exponential feeds and sophisticated event triggered processes. Combining this reactor into an automated array of reactors will ultimately be part of a high throughput process development strategy. This will combine upstream, small scale purification with rapid analytics that will dramatically shorten timelines and costs of developing biological processes. Biotechnol. Bioeng. 2013;110: 3126–3138. © 2013 Wiley Periodicals, Inc.